Analysis of Government Expenditure and Private Investment on Economic Growth in Manado City - Pradipta Mandasari Parasan; Viviane Manoppo (Journal of International Conference Proceedings (JICP), 2022)
Regional Economic Development requires an important role from the Government and the Private Sector in driving the Economy in order to Increase Economic Growth as an Indicator of the Success of a Region. The Government through the allocation of Government Expenditure, and Private Parties through Domestic Investment and Foreign Investment are expected to be able to support regional economic growth. This study intends to examine how government spending and private investment affect Manado City's economic growth., the data used is secondary data from 2012-2021 obtained from the Manado Central Statistics Agency and the Manado City PTSP Investment Office. Ordinary Least Square (OLS), a multiple linear regression model, and the Eviews program were employed as the analysis approach in this study. The findings indicated that private investment has a significant influence on economic growth whereas government spending has no significant impact. Then, both public and private investment have an impact on economic growth.Keywords: Economic Growth, Government Expenditure, Private Investment